High Pressure–Amplitude Ratio Ultrasonic Spot Welding of Thermoplastic Carbon Fiber‐Reinforced Epoxy. Issue 2 (14th September 2021) - Qin, Zhiwei; Zhou, Li; Liu, Shan; Meng, Xiangchen; Li, Junchen; Xie, Yuming; Song, Xiaoguo; Zhang, Hongming; Huang, Yongxian
Abstract : Thermoplastic carbon fiber‐reinforced epoxy has potential in the fields of aerospace, vehicle, and medical equipment, due to nontoxicity, adequate cost savings, and outstanding mechanical properties. Sensitivity to welding heat of the thermoplastic carbon fiber‐reinforced epoxy is an urgent issue due to the low glass transition temperature ( T g ). High pressure–amplitude ratio ultrasonic spot welding is used to join the low T g thermoplastic carbon fiber‐reinforced epoxy, which provided sufficient energy and pressure for suppressing the vibration and eliminating the stress relaxation to improve the stability of the material to welding heat. The molten area increased at the interface, whereas the entanglement of molecular chains was promoted under adequate pressure. The tensile shear force reached 4.6 kN with the welding pressure of 4.8 MPa, the amplitude of 44.1 μm and the welding time of 800 ms. The primary formation mechanism includes bonding of polymer, tangling of carbon fibers, and polymer, and strengthening between polymeric layers. The high pressure–amplitude ratio ultrasonic spot welding has the feasible and potential to join the low T g thermoplastic composites. Abstract : The dissipated power–time curve and the entanglement of molecular chains at four different stages are shown. The severe entanglement of molecular chains occurs at stage 3 because the welding pressure suppresses the vibration and eliminates the stress relaxation. The tensile shear force reaches 4.6 kN with the application of high pressure–amplitude ratio ultrasonic spot welding.